Analysis of the influence of peripheral vision indicators on blocking effectiveness in qualified volleyball players - N.V. , Lutkova; Yu.M. , Makarov; N.V., Pakholkova; M.N., Larionova (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the influence of peripheral vision on the effectiveness of blocking in qualified volleyball players. Methods and structure of the study. During the experimental research, an assessment was made of the effectiveness of the blocking actions of volleyball players from youth teams participating in the Saint Petersburg Championship 2024-2025. The analytical processing of data was carried out on the basis of 22 matches. At the first stage, the initial peripheral vision indicators of the volleyball players and the effectiveness of their actions at the block were determined. The Foerster perimeter method (white marker) was used as the main method for assessing peripheral vision. At the second stage, the experiment participants were offered specially developed sets of exercises aimed at improving the capacity of their peripheral vision and the influence of these indicators on blocking effectiveness. The study involved 22 volleyball players from the teams of the 'Ekran' Specialised Children's and Youth Sports School of the Olympic Reserve and the V.A. Platonov Specialised Children's and Youth Sports School of the Olympic Reserve No. 1 of the Kalininsky District, Saint Petersburg. Results and conclusions. (1) The results of the study revealed the homogeneity (similarity) of the initial peripheral vision indicators of the volleyball players in both teams across eight control measurement points for the left and right eye. (2) Three main thematic sets of exercises aimed at the development of peripheral vision were identified (for the expansion of the field of vision without motor actions; for actions with two balls; and for movements with the ball). (3) It was revealed that an increase in the indicators characterising the development of the volleyball players' peripheral vision across all eight measurements for both eyes significantly improves the effectiveness of their blocking in the course of competitive activity. (4) The implementation of special exercises for the development of peripheral vision made it possible to achieve a significant increase in the effectiveness of blocking: the effectiveness indicator in the experimental group increased from 24.6±0.77% to 27.3±0.78%. At the 0.05 significance level, the statistical reliability of the differences between the average final values of the experimental (27.3±0.78%) and control (24.65±0.81%) groups was confirmed.